The عہدِرسالتﷺ میں جمعِ قرآن اورکتابتِ وحی کےلیےسیدناامیر معاویہ رضی اللہ عنہ کی خدمات؛ایک تجزیاتی مطالعہ: The collection of the Qur'an in the prophetical life & the services of Syed Amir Muawiya (R.A.) for writing of revelation - Ahmad, Syed Ashfaq; Muawia, Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
At the time of the revelation of the Qur'an, however, there was lack of inventions. Pens and paper were hardly available, but people were familiar with the ways of writing books in those days. There were also paper industries and Yahood & Nasara had written Books of theirs. Allah Ta'ala has taken responsibility for the safety of the Holy Qur'an. This responsibility for the safety of the Holy Quran is in two ways. Either in the form of a memorizer or in a book form, the process of writing the Holy Quran had started during the era of Prophet Muhammad (ﷺ) When a verse was revealed to him(ﷺ), he called the writers of revelation and write down that verse, The Holy Quran was written on palm branches, bones, stones and pieces of leather. The complete Qur'an was written during the Prophet's era, to keep the Qur'an safe, the writing of the Qur'an was arranged very carefully, Some of the Companions were dedicated to write the Revelation, who used to write down the Revelation, At the time of the revelation of each verse, he used to collect it in order. Hazrat Abu Bakr Siddique, Hazrat Umar, Hazrat Usman Ghani, Hazrat Ali, Hazrat Zaid bin Thabit, Hazrat Ameer Muawiya, Hazrat Thabit bin Qais and Hazrat Khalid bin Walid are among those who wrote the Holy Quran. The position and rank of these writers of revelation is very high, these writers of revelation are highly praised in the Holy Quran, Hazrat Ameer Muawiya also has a very high position among these writers of revelations, who were dedicated to the writings of revelations. After accepting Islam, Ameer Muawiyah stayed with the Prophet, and always remains forefront to write the revelation, many reliable hadiths are witnesses to this, these services of Hazrat Ameer Muawiya for writing revelations are great pride for Muslims. Keywords: Holy Quran, verses, revelation, collection, dedicate, Write, Hazrat Ameer Muawiya